Peran Strategis Ekonomi Syariah dalam Pembangunan Nasional: Analisis Prinsip, Implementasi, dan Tantangan Kontemporer - Syah Wardi (Sharia Law and Justice Journal, 2025)
Islamic economics is an economic system based on Islamic principles such as justice, balance, the prohibition of usury (riba), uncertainty (gharar), and gambling (maisir), as well as the implementation of profit-and-loss sharing. This article aims to analyze the role of Islamic economics in national development by highlighting the contributions of Islamic banking, SME empowerment, social-economic instruments (zakat, infaq, sadaqah, waqf), and the challenges and opportunities in the digital era. This research employs a library research method with a descriptive-analytical approach. The findings reveal that Islamic economics has great potential to realize sustainable, inclusive, and equitable development. Its contributions are evident in strengthening the Islamic financial system, empowering the real sector, and enhancing social welfare through Islamic economic instruments. Nevertheless, several challenges remain, such as low public literacy, suboptimal regulations, and limited human resources. Therefore, synergy between the government, academics, practitioners, and society is needed to optimize the role of Islamic economics in national development.